PRODUCTIVE ZAKAT TOWARDS ECONOMIC ARMALAH IMPROVEMENT OF MAKASSAR CITY COMMUNITY IN YATIM MANDIRI MAKASSAR - Muhammad Maulana; Faturrahman Faturrahman; Sirajuddin Sirajuddin (Universitas Muhammadiyah Surakarta, 2023)
LAZNAS Yatim Mandiri Makassar distributes productive zakat to overcome economic disparities or poverty that occurs to the armalah (widow) of the Antang community, sub-district It is hoped that at Manggala, the underprivileged family will become more prosperous and able to be independent. This type of research is a case study with a qualitative approach, primary data sources are sourced from program staff and branch heads and admin and financial staff of LAZNAS Yatim Mandiri Makassar and armah as members of the BISA program (Bunda Mandiri Sejahtera). While secondary data sources are data sourced from institutions including annual reports on institutional profiles, institutional vision and mission, institutional programs, and journals used to support and complete primary data. The productive zakat management model of the Bunda BISA program has been proven to have the effect of increasing the economy of the community of Antang sub-district Manggala Makassar City and the gifts given are the provision of business capital, spiritual guidance, and providing knowledge related to managing a business properly and providing necessities to Armala every month, with this effort they can fulfill their life needs.